Black- White Differences in Predictive Validity of Depressive Symptoms for Subsequent Major Depression - Ehsan eMoazen Zadeh; Shervin eAssari (Frontiers Media S.A., 2016)
BackgroundBlack- White differences are shown in psychosocial and medical correlates of depressive symptoms and major depressive disorder (MDD). The current longitudinal study compared Blacks and Whites for the association between baseline depressive symptoms and subsequent risk of MDD 15 years later. MethodsData came from the Americans' Changing Lives (ACL) Study that followed 3,361 individuals (2,205 Whites and 1,156 Blacks) from 1986 to 2001. Predictor was baseline depressive symptoms measured using an 11-item Center for Epidemiological Studies-Depression (CES-D) in 1986. Outcome was 12 month MDD measured using the Composite International Diagnostic Interview (CIDI) at 2001. Covariates included baseline socio-demographics, financial difficulty, chronic medical conditions, and self-rated health (SRH) measured at 1986. We used logistic regression to evaluate the association between baseline CES-D score and CIDI-based MDD 15 years later net of demographics, SES, CMCs and SRH. The models were applied in the pooled sample, as well as Blacks and Whites. We also reported data on reliability and factor structure of CES-D based on ethnicity. ResultsAccording to the logistic regression models, baseline CES-D scores were predictive of subsequent CIDI- based 12 month MDD 15 years later among Whites but not Blacks. Ethnic differences in predictive validity of CES-D scores on MDD could not be attributed to the ethnic differences in reliability of the CES-D which was even higher for Blacks than Whites. ConclusionBlack-White differences exist in the association between baseline depressive symptoms and subsequent risk of MDD over 15 years. Ethnic differences in the longitudinal link between baseline CES-D and subsequent risk of MDD among Blacks may explain some of the Black - White differences in social, psychological, and medical correlates of depressive symptoms and depression. Future research is still needed to compare Blacks and Whites for confirmatory factor analysis of the CES-D.